Gearing up for battle: Harnessing adaptive T cell immunity against gram-negative pneumonia - Gao, Catherine A.; Morales-Nebreda, Luisa; Pickens, Chiagozie I. (Frontiers in Cellular and Infection Microbiology, 2022)
Pneumonia is one of the leading causes of morbidity and mortality worldwide and Gram-negative bacteria are a major cause of severe pneumonia. Despite advances in diagnosis and treatment, the rise of multidrug-resistant organisms and hypervirulent strains demonstrates that there will continue to be challenges with traditional treatment strategies using antibiotics. Hence, an alternative approach is to focus on the disease tolerance components that mediate immune resistance and enhance tissue resilience. Adaptive immunity plays a pivotal role in modulating these processes, thus affecting the incidence and severity of pneumonia. In this review, we focus on the adaptive T cell responses to pneumonia induced by Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. We highlight key factors in these responses that have potential for therapeutic targeting, as well as the gaps in current knowledge to be focused on in future work.